Exfoliation of bulk inorganic layered materials into nanosheets by the rapid quenching method and their electrochemical performance - Chakravarty, Disha; Late, Dattatray J. (European Journal of Inorganic Chemistry, 2015)
We report herein the results of our investigations on the synthesis of transition-metal dichalcogenide (TMDC) semiconductor layered materials of MoS2, WS2, MoSe2, and WSe2 by the rapid quenching method. The bulk powders were added to deionized water in a polypropylene tube and subsequently flushed with argon gas. Thirty rapid freezing (30 s in a liquid nitrogen bath) and heating (20 min in an oil bath at 60 degrees C) cycles were then carried out. The reaction product was obtained in a yield in excess of 60 wt.-%, which indicates that the method can be utilized on an industrial scale for the production of 2D nanosheets. The as-synthesized products were then characterized by TEM, which revealed nanosheet-like morphologies. Raman spectroscopy confirmed the high quality of the nanosheet samples. The exfoliated samples also showed good electrochemical performance. Of the TMDC samples investigated, the WSe2 nanosheets were found to give the best performance due to their uniform morphology, large surface area, and fewest number of defects.
Keywords: chalcogenides; Electrochemistry; Layered compounds; Molybdenum; Nanostructures; Tungsten

Microwave-assisted synthesis of few-layered TaTe2 and its application as supercapacitor - Chakravarty, Disha; Kumar, Praveen; Ugale, Vaishali S.; Late, Dattatray J. (European Journal of Inorganic Chemistry, 2015)
We report a simple and rapid microwave-assisted synthesis of tantalum telluride (TaTe2) nanosheets. The ratio of tantalum pentachloride (TaCl5) and elemental tellurium (Te) powder were adjusted in the presence of NaBH4 in such a way as to obtain the TaTe2 nanosheet. The samples were characterized by various techniques such as scanning electron microscopy (SEM), transmission electron microscopy (TEM), atomic force microscopy (AFM), UV/Vis spectroscopy, photoluminescence (PL) spectroscopy, and XRD. Our SEM, TEM, and AFM results show the formation of sheet-like morphology, while the XRD data confirms the high crystalline quality and stable phase of the TaTe2 formed. The supercapacitor cells were fabricated by using TaTe2 nanosheets as anode material, platinum metal wire as a counterelectrode, and Ag/AgCl as reference electrode. The calculated coulombic efficiency is more than 95%, while the cycle-to-cycle decrease in capacity is less than 5%. The maximum discharge or charging capacity is below 2.4 Wh/kg, which is an ideal characteristic for achieving supercapacitor behavior.
Keywords: Microwave chemistry; Nanostructures; Supercapacitors; Tantalum; Tellurium